2013
DOI: 10.1111/cas.12160
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA in the pathogenesis of malignant lymphoma

Abstract: MicroRNA (miRNA) are non-coding regulatory RNA usually consisting of 20À24 nucleotides. Over the past decade, increases and decreases in miRNA expression have been shown to associate with various types of disease, including cancer. The first two known miRNA aberrations resulted from altered expression of DLEU2 and C13orf25 in hematological malignancies. DLEU2, which encodes miR-15a and miR-16-1, was discovered from 13q14 deletion in chronic lymphocytic leukemia, while C13orf25, which encodes six mature miRNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 81 publications
(184 reference statements)
2
35
0
1
Order By: Relevance
“…Next, we demonstrated the overexpression of miR-155, miR-200c, miR-130a, miR-125b and miR-21 and underexpression of miR-29c, miR-451 and miR-145 in DLBCL serum. Notably, deregulation profiling of most of these miRNAs in DLBCL has been reported in a previous study (12), with the exception of miR-130a and miR-451. In this study, we first demonstrated the deregulated expression of circulating miR-130a and miR-451 in DLBCL.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Next, we demonstrated the overexpression of miR-155, miR-200c, miR-130a, miR-125b and miR-21 and underexpression of miR-29c, miR-451 and miR-145 in DLBCL serum. Notably, deregulation profiling of most of these miRNAs in DLBCL has been reported in a previous study (12), with the exception of miR-130a and miR-451. In this study, we first demonstrated the deregulated expression of circulating miR-130a and miR-451 in DLBCL.…”
Section: Discussionsupporting
confidence: 52%
“…microRNAs (miRNAs) are small, non-coding RNAs that regulate gene expression at the post-transcriptional level through sequence complementation with target mRNAs to repress transcription or induce mRNA degradation (10). Previous studies have determined a link between the expression of miRNAs and cancer pathogenesis, and miRNAs have revealed themselves to be significant biomarkers for tumor diagnosis, invasion, metastasis and evaluation of prognosis in certain types of tumors (11)(12)(13)(14). However, chemoresistance-related miRNA expression profiles in DLBCL are reported less often.…”
Section: Introductionmentioning
confidence: 99%
“…1D and E). Moreover, we observed that MCL1 and BCL2, which are validated miR-29s targets (6,16), were decreased in drug-treated gastric cancer cells ( Fig. 1F and G).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, miR-21, miR-155 and miR-17-92 clusters have been acknowledged as oncogenic miRNA, which are believed to target tumor-suppressive molecules in various types of tumor, including glioblastomas, cholangiocarcinomas, lung cancer, breast cancer and colon cancer (10). Furthermore, overexpression of miR-21, miR-155 and miR-17-92 may be observed in lymphomas derived from B cells, T cells or natural killer cells (8,11,12). Notably, miR-21 has a vital role in regulating the chemosensitivity of DLBCL cells (13) and Bcl-2, a tumor-associated and anti-apoptotic molecule, has a key role in the chemoresistance of NHL and has been considered as a prognostic biomarker for DLBCL (14).…”
Section: Introductionmentioning
confidence: 99%